Organisational Growth and Performance: Special Reference to Commercial Bank of Ceylon PLC in Sri Lanka - Priya, K.; Thusha, S. (JUICE- 2012 University of Jaffna, 2012)
This study was undertaken with the objective of find out the relationship between Organisational Growth and Performance: The special reference to Commercial Bank of Ceylon PLC (CBC) in Sri Lanka. Using a multiple regression analysis was examined for the period of 1996-2010 (15Years). In this study, dependent variable that is, net profit, operating profit, return on investment, return on equity, return on average asset, return on average shareholder. The independent variables are measured by number of employees, number of advances, number of depositors and gross income. Secondary data were collected for this study. Data were gathered from books, journals and annual reports etc. The present study is confined only to the CBC PLC as a whole. Now a day’s CBC PLC is the largest and the most admired private bank which is contributed to the development of economy of Sri Lanka. Banks and other financial institutions are a unique set of business firms whose assets and Liabilities, regulatory restrictions, economic functions and operating make them an important subject of research, particularly in the conditions of the emerging financial sectors in Sri Lanka. Banks’ performance monitoring, analysis and control needs special analysis in respect to their operation and performance results from the viewpoint of different audiences, like investors/owners, regulators, customers/clients, and management themselves. Some historical notes on the development of the banking system and the financial sectors are presented in this research paper. Different versions of financial ratio analysis are used for the bank performance analysis using financial statement items as initial data sources. The usage of a modified version applied in this research paper. Empirical results of the commercial banking system performance analysis are also presented.
Keywords: Organisational growth; Performance; Sustainability